UPAYA PENGASUH DALAM MENGEMBANGKAN PERILAKU DISIPLIN ANAK PANTI ASUHAN AISYIYAH MANINJAU - Hatika Mutiasari; Linda Yarni (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2023)
The first education of a child is parents, parents forbid how children behave and behave, every human being has a different way of shaping children's behavior, but it is different from children who live in foster care, children who are in orphanages are children who have deficiencies in the economy , children who do not have parents and others, those who are in orphanages are educated by foster parents or better known as caregivers. The focus of the researcher's research is to find out the efforts of caregivers in developing the discipline of orphanage children, in orphanages the attitudes and behavior of children are formed, namely how they work and behave, especially in forming child discipline. Caregivers have an important role in educating orphans both in small and big matters, various efforts are made by caregivers so that they can make foster children become good individuals and be able to be responsible for what is assigned to them so that they become trained. At the Aisyiyah Orphanage, giving punishment is the most frequently used effort by caregivers to make the orphanage children discipline, especially for children who have been repeatedly advised but are not deterred. This research method is a qualitative research with a descriptive approach